2010
DOI: 10.3109/15622970902960897
|View full text |Cite
|
Sign up to set email alerts
|

The influence of anaesthetic medication on safety, tolerability and clinical effectiveness of electroconvulsive therapy

Abstract: Our study supports the hypothesis that inducting anaesthetic agents have a different impact on seizure duration, ictal and postictal electrophysiological indices and clinical efficacy of ECT. Compared to thiopental, which has been established as a standard anaesthetic during ECT, also the modern anaesthetic propofol is a suitable inducting agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
1
7
1
Order By: Relevance
“…Furthermore, propofol was found not to compromise patient psychiatric or behavioral outcome after ECT, as compared with thiopental [36], and it even facilitated significantly better clinical effectiveness than methohexital or etomidate [37]. Based on the behavioral data, our results further confirmed that propofol neither affected depression (no differences were found between groups D and P) nor influenced the antidepressant effectiveness of ECT by itself (no differences were found between groups E and M; see Figs.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, propofol was found not to compromise patient psychiatric or behavioral outcome after ECT, as compared with thiopental [36], and it even facilitated significantly better clinical effectiveness than methohexital or etomidate [37]. Based on the behavioral data, our results further confirmed that propofol neither affected depression (no differences were found between groups D and P) nor influenced the antidepressant effectiveness of ECT by itself (no differences were found between groups E and M; see Figs.…”
Section: Discussionsupporting
confidence: 92%
“…1 Stimulation parameters such as total charge dose and electrode placement have been shown to affect ECT response. 2 Another important variable that could influence efficacy is the anesthetic agent because general anesthesia required for ECT is induced by barbiturates or other hypnotics, many of which possess anticonvulsant properties, 3,4 which could interfere with seizure quality and length, affecting clinical outcome. Therefore, determining the optimal anesthetic agent for the procedure is a critical albeit unresolved issue.…”
mentioning
confidence: 99%
“…8,26 Recommendations about the use of propofol in ECT have also varied considerably; some authors advise against its routine use, 17,20,21,27 whereas others find it to be a suitable alternative to methohexital. 4,13,25,28 During 2002Y2003, a nationwide shortage of methohexital forced psychiatrists to use alternative induction agents for ECT. 27,29 At Johns Hopkins, we switched to propofol for ECT administration.…”
mentioning
confidence: 99%
“…Extensive literature has evaluated alternative anesthetic agents, including etomidate, propofol, and ketamine, in the ECT setting; however, no agent has been clearly favoured as a first-line alternative to thiopental. [6][7][8] Previous studies showed no difference in efficacy of ECT with different anesthetics. The retrospective analysis of ECT in the current study showed that etomidate and ketamine were prescribed most often when thiopental became unavailable.…”
Section: Discussionmentioning
confidence: 99%